Knowledge and Application of Pharmacist Ethics Practices in Pekalongan Regency - Adistya, Diva; Da’i, Muhammad (Newinera Publisher, 2024)
This study aims to determine the knowledge and application of pharmacist ethical practices in Pekalongan Regency. This study is a type of observational descriptive study, the population in this study is pharmacists who practice in Pekalongan Regency as many as 129 using purposive sampling, the sample in this study was obtained as many as 100 respondents. The instrument used in this study was a questionnaire. This research will be conducted in Pekalongan district from October to December 2023. Data analysis of this study was carried out by descriptive analysis on SPSS software. The results showed that out of 100 respondents, 97 respondents (97%) had good knowledge about pharmacist ethical practices. However, out of 100 respondents, 52 respondents (52%) dominated the application of pharmacy ethical practices in the less category. It can be concluded that although pharmacists have good knowledge in pharmacist ethical practices, in the application of pharmacist ethical practices compared to the best, which is less.